Nitric oxide synthase 2 (NOS2) expression in histologically normal margins of oral squamous cell carcinoma - Morelatto, Rosana (2014)
Morelatto, Rosana. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Estomatología; Argentina.